Social media reviews as influencers in the purchase intention of skincare - Alano, Samantha Nicole B., Balangquit, Samantha M., Enriquez, Jorge Mellodie M., Galang, Ma. Angelica M., Guerrero, Ma. Florelene A., Imutan, Ryanna Angelie S., Puno, Rose Lynne D. 4 0 16; 5
Abstract Social media reviews have grown in strength as major influencers in molding people's purchasing intentions. Individuals now have access to a wide selection of product reviews and suggestions from peers, influencers, and experts. This research paper analyzes social media as influencers in the purchase intention of skincare products by young professionals. In order to accomplish the objective of the study, a total of 100 respondents completed an online survey questionnaire through Google Forms, which was then analyzed in SPSS. The results of the study show that all of the study's variables namely, Reviews with Images, Reviews with Emotional Content, Review Quality, Information Overload, Information Helpfulness, Price, Convenience, Information, Customer Knowledge, and Perceived Value significantly impact the customers' purchasing intentions. Social media reviews have a significant effect on consumer purchasing decisions as they provide useful insights, opinions, and experiences about goods or services. Keywords: Social Media Reviews, Purchase Intention, Skincare Products
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2